Cover Feature: An Organometallic Gold(I) Bis‐N‐Heterocyclic Carbene Complex with Multimodal Activity in Ovarian Cancer Cells (Chem. Eur. J. 67/2020). Issue 67 (3rd November 2020) - Meier‐Menches, Samuel M.; Neuditschko, Benjamin; Zappe, Katja; Schaier, Martin; Gerner, Marlene C.; Schmetterer, Klaus G.; Del Favero, Giorgia; Bonsignore, Riccardo; Cichna‐Markl, Margit; Koellensperger, Gunda; Casini, Angela; Gerner, Christopher
Abstract : A cationic Au I N‐heterocyclic carbene complex featuring caffeine‐based ligands has shown potent and selective anticancer effects in ovarian cancer cells. This organogold compound is remarkably stable in physiological conditions. Therefore, the observed therapeutic effects are mainly due to non‐covalent interactions of the gold compound with its pharmacological targets. Among the latter, DNA secondary structures—G‐quadruplexes—play a pivotal role in the mechanisms of anticancer action. More information can be found in the Full Paper by S. M. Meier‐Menches, A. Casini, C. Gerner, et al. on page 15528 .